Providing Elderly Gymnastics as an Initial Step to Prevent Stroke in the Elderly in Rw 15 Gendingan, Jebres, Surakarta - Rohmah, Asita (Prosiding University Research Colloquium, 2023)
Background: Elderly or elderly is the last stage in the process of human growth and development. At this stage the elderly experience a decrease in body function. The elderly began to complain of problems with their bodies such as knee pain, lower back pain, hypertension and many more. As technology advances in this modern era and the COVID-19 pandemic, the elderly experience a decrease in physical activity. The reduced physical activity experienced by the elderly can trigger other diseases and worsen the condition of the elderly. Giving elderly exercise is not only to make the elderly move but also able to be the first step to prevent other diseases including stroke. Objective: This outreach activity aims to introduce elderly exercise as the first step in preventing stroke. Method: The method used is counseling and application of elderly exercise. Results: Based on the results of observations, it was found that the elderly had hypertension (70%) and the elderly with normal blood pressure (30%). After being given exercise for the elderly, there was a good response, the elderly became happier and able to stimulate physical health.